First fossil record of a nymph (Ephemeroptera, Teloganellidae) from the Indian subcontinent - Agnihotri, Priya; Chandra, Kajal; Shukla, Anumeha; Singh, Hukam; Mehrotra, Rakesh C. (Zootaxa, 2020)
A fossil of a mayfly nymph that shows similarities with the modern genus Teloganella Ulmer, 1939 of the family Teloganellidae is recorded for the first time from the Indian subcontinent. It is systematically described from the Gurha lignite mine of Bikaner, Rajasthan which belongs to the Palana Formation (late Paleocene-early Eocene). As assignment of the fossil to a modern species of Teloganella is difficult due to indistinguishable location of gills in the impression, a new species, Teloganella gurhaensis Agnihotri et al., sp. nov. is instituted to include this fossil naiad resembling the extant Teloganella.